INFLUENCE OF INDUCED CARCINOGENESIS ON BIOLOGICAL MARKERS OF ENDOTOXEMIA - Lisnychuk, N.Ye.; Andriichuk, I.Ya.; Soroka, Yu.Ya.; Stravska, M.V.; Yavorska, S.I. (World of Medicine and Biology, 2018)
In an experement on outbred white rats was conducted a research of changes in biological markers of endogenous intoxication in the dynamics of development of induced neoplastic process. There was established the progressive formation and accumulation in the blood of the experimental animals of middle-mass molecules of different fractions: МMМ238, МMМ254, МMМ260, МMМ280. The membranedestractive effect of these protein toxins in confirmed by an increase in the erythrocyte index of intoxication.Mathematically calculated index of distribution, aromaticity index and the peptide-nucleotide index indicate on violation between the individual components of the complex of substances of low and medium molecular weight.
Keywords: Induced neoplastic process; endogenous intoxication; biological markers